Relationship Relationship between Organizational Culture and Compensation with Teacher Performance: A Case of The Islamic Vocational High School of PB Soedirman 2 - Iriansyah (Kusuma Negara Business School, 2021)
The objective of this research is to study the relationship between organizational culture and compensation with teacher performance of The Islamic Vocational High School of PB Soedirman 2. This research using a survey method that included 30 samples. Data collecting using a questionnaire and analyzed by correlation and regression. The result of the research showed that: (1) there is a positive relationship organizational culture with teacher’s performance; (2) there is a positive relationship compensation with teacher’s performance; (3) the relationship between organizational culture and compensation simultaneously with teacher's performance. It means that all of the hypotheses in this research can be accepted. This research concludes that the teacher’s performance can be improved by increasing organizational culture and compensation. Therefore, needed to make efforts for improving organizational culture and compensation.